Pengaruh Steam Quality Terhadap Produksi Minyak di PT CPI (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Crude oil is one of Earth product that obtained with various process and lifting method up to surface. Crude oil at Duri field PT CPI within into heavy oil, viscous and contain a lot of sand based on itâs characteristic, so that steam injection into reservoir is needed for making oil mobilization to well production easier. The objective of research to learn about effect of steam quality to oil production in Duri area. Research was held by varying steam generator feed water flow rate of 104 gpm and 105 gpm, steam quality variation of 72%, 73% and 74%. Steam quality sample was taken in each steam generator to be counted, then adjustment of burner positioner was needed when steam quality did not achieve. Oil production data was taken after itâs trend shown steady. Result of research were show that steam quality increment from 72% to 73%, average oil production rose up to 68 bopd and from 73% to 74%, rose up to 18 bopd. The highest steam quality effectivity in 73% at steam generator feed water flow rate of 105 gpm and fuel rate of 8550.57 Mscfd, with oil production rate of 5234.34 bopd.Keyword : reservoir, steam generator, steam quality